Lucid Dreaming Brain Network Based on Tholey’s 7 Klartraum Criteria - Holzinger, Brigitte; Mayer, Lucille (Frontiers in Psychology, 2020)
Lucid dreaming refers to a dream state characterized by the dreamers awareness of being in a dream and being able to volitionally control its content. The aim of this study was to find neurophysiological evidence for the 7 criteria of lucid dreaming proposed by Paul Tholey. Each of the criteria was analyzed separately with regard to its underlying neurocircuits. We hypothesized that not one, but many regions are involved in the state of lucid dreaming. Our results have shown a satisfactory overlap of the theoretical components and the brain regions activated during a lucid dream. During lucid dreaming, a brain network seems to emerge, that is more than the sum of its parts. Further research is needed to understand the psychoneurological underpinnings of lucid dreams.